PENGARUH SUBSTITUSI TEPUNG AMPAS TAHU TERHADAP KUALITAS BROWNIES BAKAR - Dahniar, Dahniar; Elida, Elida; Syarif, Wirnelis (Journal of Home Economics and Tourism, 2017)
This study aimed to analyze the effect of substitution of flour tofu as much as 25%, 35% and 50% of the fuel quality brownies which includes volume, shape, color, aroma, texture and taste. Pure experimental research type (true experiment) that was conducted in December 2016 and located in the workshop Catering. This type of data is primary data sourced from the five expert panelists and answer format organoleptic test. Data were analyzed with ANOVA statistical analysis, if F count> F table then continued with Duncan test. The results of the study there was no significant effect of substitution of flour pulp out of the quality of brownies fuel (volume, shape, aroma, texture and taste of flour tofu) because of F <F table, means that Ho is accepted and there is a significant effect of substitution of flour tofu to quality brownies fuel (color, sweetness and taste of chocolate) for F count> F table, means Ho rejectedThe best results based on test organoleptip is contained in X1 with flour substitution tofu as much as 25%.Keywords: Effect, Flour Substitutes Tofu Dregs and Brownies Bakar